Does supervised physical activity reduce cancer-related fatigue: a systematic review (2015)
PURPOSE: Does supervised physical activity reduce cancer-related fatigue? METHODS: Systematic review with meta-analysis of randomised trials. Participants: People diagnosed with any type of cancer, without restriction to a particular stage of diagnosis or treatment. Intervention: Supervised physical activity interventions (eg, aerobic, resistance and stretching exercise), defined as any planned or structured body movement causing an increase in energy expenditure, designed to maintain or enhance health-related outcomes, and performed with systematic frequency, intensity and duration. Outcome measures: The primary outcome measure was fatigue. Secondary outcomes were physical and functional wellbeing assessed using the Functional Assessment of Cancer Therapy FACT-Fatigue Scale, EORTC, QLQ-C30, PFS, SCFS, MFI. Methodological quality including risk of bias of the studies was evaluated using the PEDro Scale. RESULTS: Eleven studies involving 1530 participants were included in the review. The assessment of quality showed a mean score of 6.5 (SD 1.1), indicating a low overall risk of bias. The pooled effect on fatigue, calculated as a standardised mean difference (SMD) using a random-effects model, was -1.69 (95% CI -2.99 to -0.39). Beneficial reductions in fatigue were also found with combined aerobic and resistance training with supervision (SMD = -0.41, 95% CI -0.70 to -0.13) and with combined aerobic, resistance and stretching training with supervision (SMD = - 0.67, 95% CI -1.17 to -0.17). CONCLUSION: Supervised physical activity interventions reduce cancer-related fatigue. These findings suggest that combined aerobic and resistance exercise regimens with or without stretching should be included as part of rehabilitation programs for cancer survivors.